Legal Transplant in Vietnam - Quan, Nguyen Van; Cu, Vu Thanh (VNU Journal of Science: Legal Studies, 2023)
The interplay of legal systems has existed for thousands of years. In the contemporary context, globalization promotes interaction between legal systems. Legal comparatists have long developed the “legal transplant” theory to investigate foreign legal borrowing cases. However, scholars have not looked into this phenomenon in Vietnam thoroughly. The article introduces the theoretical framework of legal transplant. It then considers the practice of legal transplant in Vietnam in several legal fields to point out the decisive factors of the success or failure of the legal transplant.